Endovascular intravascular intervention for central venous stenosis in maintenance hemodialysis patients: a retrospective observational study - Tao, Yiming; Wang, Jianyun; Ma, Jianchao; Peng, Siqi; Chen, Boxi; Deng, Shuting; Yuan, Ye; Jiang, Nan; Wen, Sichun; Li, Bohou; Wu, Qiong; Xu, Lixia; et al. (Frontiers in Cardiovascular Medicine, 2024)
BackgroundThe number of people undergoing maintenance hemodialysis is increasing rapidly worldwide. Central vein stenosis (CVS) is a common vascular complication in undergoing hemodialysis, especially those with a history of catheterization. This study aimed to investigate the characteristics of CVS and the clinical effectiveness of percutaneous transluminal angioplasty (PTA) alone and sequential percutaneous transluminal stenting (PTS) in hemodialysis patients with CVS.MethodsA retrospective analysis of 26 cases of endovascular intervention for CVS using PTA alone or sequential PTS was performed. The characteristics of CVS and the clinical effectiveness of these procedures were evaluated.ResultsThis study included 26 hemodialysis patients who presented with symptomatic CVS. Of these 26 patients, 53.85% were male, and their mean age was approximately 54.96 years. All the patients had a history of catheter placement or pacemaker implantation. The incidence of brachiocephalic vein stenosis was significantly higher than that of subclavian vein stenosis (46.16% vs. 26.92%). Based on the degree of stenosis and elastic retraction, these patients were administered PTA alone or sequential PTS. There was no difference in patient age, hemodialysis time, catheter retention time, or stenosis length between the PTA alone and sequential PTS groups. However, the degree of venous stenosis in the PTS group was more severe than that in the PTA alone group. The primary patency rates in the sequential PTS and PTA alone groups were 94.12% and 100% at 3 months; 88.24% and 88.89% at 6 months; 75.00% and 85.71% at 9 months; and 66.67% and 71.43% at 12 months, respectively. It is worth noting that for 7 patients with complete occlusion of the brachiocephalic vein, we used sharp recanalization technology and stenting placement, with patency rates of 85.71% and 71.43% at 6 and 12 months, respectively.ConclusionsPTA alone is recommended for patients with less than 50% central venous elastic retraction, while sequential PTS is recommended for patients with ≥ 50% central venous elastic retraction. PTA and PTS are safe and effective methods for the treatment of CVS in patients undergoing hemodialysis.